Institutional and politico-administrative responses to armed conflicts - Brillantes, Alex B., Jr.; Tiusongco, Jose O. (2005)
The conflict between the Autonomous Region in Muslim Mindanao (ARMM) and the government of the Republic of the Philippines (GRP) has been a long-time crisis. It encompasses the vague delineation of the policies imposed on ARMM by the government, indictment by the Mindanao people especially the Muslims of the government's failure to deliver human development in general and social services in particular and the unsuccessful series of peace settlements. As a result, different groups waged secessionist wars with the government; hostility in the region; underdevelopment, poverty, economic isolation, poor quality of education and emotional turmoil continue to prevail. The study discusses the institutional and politico-administrative responses should be accompanied by comprehensive and integrated capacity building efforts, continued capacity building of young Muslim leaders, training for Armed Forces of the Philippines (AFP), careful examination of the continuity and discontinuity of certain policies that have negative effects, and considering Federalism as an option.
Keywords: Armed Forces of the Philippines; Autonomous Region in Muslim Mindanao; Insurgency; Reconciliation